Implementation of School-Based Trauma Healing Interventions to Improve Stress Coping of Students Experiencing Grief at Madrasah Tsanawiyah Kediri - Tatik Imadatus Sa'adati; Karisma Dewi Puspasari; Dewi Laila Wati; Ratih Setya Mahardika (Journal An-Nafs: Kajian Penelitian Psikologi, 2026)
This study aims to describe the implementation of a school-based Mental Health and Psychosocial Support (MHPSS) program and explore students’ psychological responses following grief after a traumatic incident at a Madrasah Tsanawiyah in Kediri. The study employed a descriptive exploratory approach involving 38 eighth-grade students who were classmates of a victim of a violent incident. Participants were selected using purposive sampling. Data were collected using the Self-Reporting Questionnaire-20 (SRQ-20) to describe students’ psychological conditions and through written reflections to explore students’ experiences following participation in the program. The MHPSS program consisted of psychoeducation, relaxation training and brain gym exercises, positive thinking development, and peer-supported group discussions. The initial assessment showed that 23 of 38 students (60.5%) experienced psychological distress. The most frequently identified symptoms were reduced energy (43.5%) and depressive symptoms (39.1%), followed by anxiety symptoms (13.0%) and somatic symptoms (4.4%). Analysis of students’ written reflections identified themes of emotional relief, increased emotional awareness, opportunities for emotional expression, acceptance of the incident, and perceived peer support. However, some students continued to report fear and anxiety following the program. The findings provide a descriptive overview of students’ psychological conditions following a traumatic incident and suggest that school-based MHPSS activities may offer supportive opportunities for emotional expression and psychosocial adjustment. The study highlights the importance of integrating trauma-informed psychosocial support within school systems, particularly in madrasah settings. Future studies employing standardised post-intervention measures and comparison groups are needed to evaluate intervention effectiveness more rigorously.